An Eye Tracking Study on the Reception of Second-Person Pronouns in English-Chinese Advertisement Translation - Ying Cui; Xiao Liu (SAGE Open)
Second-person pronouns (SPs) address readers directly, and they are widely used in the advertising discourse. SPs are often handled flexibly in English-Chinese advertisement translation, and SPs may be added to Chinese translations even when the original texts do not have second-person reference. This study has explored Chinese readers’ reception of SPs via pupillometry. Thirty-seven participants were recruited for an eye-tracking experiment. Two parallel Chinese versions of 20 English advertisements were prepared, one set with an SP and the other one without it. After the eye-tracking experiment, participants filled out a questionnaire and rated their impression of the texts on a five-point scale. Data analysis shows that pupil dilation was significantly higher when participants read the SP version, with longer fixation duration and more fixation counts. In addition, their subjective ratings of the SP version were also higher, meaning that they liked the version better. Such results suggest that using SPs in Chinese advertisement translation is an effective method of attracting readers.